Recent progress on the microbial mitigation of heavy metal stress in soybean: overview and implications - Shaffique, Shifa; Hussain, Saddam; Kang, Sang-Mo; Imran, Muhammad; Kwon, Eun-Hae; Khan, Muhammad Aaqil; Lee, In-Jung (Frontiers in Plant Science, 2023)
Plants are adapted to defend themselves in a series of programming, reprogramming, and stress tolerance against various environmental stresses, such as heavy metal stress. Beneficial microbes play an essential role in mitigating heavy metal stress. We present a literature review describing the initiation of heavy metal tolerance mediated by plant inoculation with endophytes and plant growth-promoting rhizobacteria and the plant transduction pathways. Identification via sensing the annotation and contemporary changes from molecular to genomics. Overall, microbial inoculation is essential in mediating plant protection responses to heavy metal stress produced by a fluctuating climate.